2013
DOI: 10.1038/emboj.2013.236
|View full text |Cite
|
Sign up to set email alerts
|

SNAIL and miR-34a feed-forward regulation of ZNF281/ZBP99 promotes epithelial-mesenchymal transition

Abstract: Here, we show that expression of ZNF281/ZBP-99 is controlled by SNAIL and miR-34a/b/c in a coherent feedforward loop: the epithelial-mesenchymal transition (EMT) inducing factor SNAIL directly induces ZNF281 transcription and represses miR-34a/b/c, thereby alleviating ZNF281 mRNA from direct down-regulation by miR-34. Furthermore, p53 activation resulted in a miR-34a-dependent repression of ZNF281. Ectopic ZNF281 expression in colorectal cancer (CRC) cells induced EMT by directly activating SNAIL, and was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 75 publications
7
141
0
Order By: Relevance
“…Among other direct miR-34a targets that induce cancer cell invasion are c-KIT (51), AXL (52), and c-MET (53). We recently showed that the zinc finger 281 protein (ZNF281) is also an important miR-34 target with respect to EMT (54). We demonstrated that the expression of ZNF281 is controlled by miR-34 and SNAIL in a coherent feed-forward loop, where SNAIL and ZNF281 induce each other, whereas miR-34 can directly repress both of them.…”
Section: Methodsmentioning
confidence: 99%
“…Among other direct miR-34a targets that induce cancer cell invasion are c-KIT (51), AXL (52), and c-MET (53). We recently showed that the zinc finger 281 protein (ZNF281) is also an important miR-34 target with respect to EMT (54). We demonstrated that the expression of ZNF281 is controlled by miR-34 and SNAIL in a coherent feed-forward loop, where SNAIL and ZNF281 induce each other, whereas miR-34 can directly repress both of them.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, our study revealed a direct activator role for Drosophila Snail, a function that is seemingly conserved from flies to humans (Sakai et al 2006;Stemmer et al 2008;Reece-Hoyes et al 2009;Hu et al 2010;Tao et al 2011;Wels et al 2011;Hahn et al 2013) and places the Snail family of proteins in the category of dually acting TFs.…”
Section: A New View Of How Snail Regulates Diverse Developmental Procmentioning
confidence: 99%
“…Although the studies in HepG2 cells and in quail show that full activation by Snail requires a partner factor, vertebrate Snail proteins can also activate on their own in vitro (Huang et al 2009;Tao et al 2011;Wels et al 2011;Hahn et al 2013). Potential synergistic effects have not been analyzed in these studies.…”
Section: Motif Prediction Identifies a New Motif Essential For Snail mentioning
confidence: 99%
See 1 more Smart Citation
“…The EMT process functions necessarily in the embryonic development by differentiating into different tissues, facilitating the morphological formation of various organs and regenerating tissues after injury. The induction of EMT can be triggered by many factors ranging from cytokines including TGF-β, and types of transcription factors such as Twist [56][57][58], Snail [59][60][61], Slug [62,63] and KLF8 [64][65][66], to various signaling pathways encompassing the ones we have discussed above, and certain exogenous drug agents will be discussed below.…”
Section: The Notch Pathwaymentioning
confidence: 99%